An observational study of vascular endothelial growth factor inhibitors as second-line treatment for metastatic colorectal cancer treated with bevacizumab plus FOLFIRI beyond progression: the association with RAS mutation and tumor sidedness - Tsai, Hsiang-Lin; Huang, Ching-Wen; Ma, Cheng-Jen; Su, Wei-Chih; Chang, Tsung-Kun; Chen, Po-Jung; Yeh, Yung-Sung; Wang, Jaw-Yuan (Translational Cancer Research; Vol 8, No 6 (October 30, 2019): Translational Cancer Research, 2019)
Background: The BRiTE and ARIES studies suggested that the continued use of bevacizumab beyond progression (BBP) was beneficial. This study investigated the efficacy and safety of the vascular endothelial growth factor inhibitors (VEGFis) bevacizumab and aflibercept as second-line treatments for patients with metastatic colorectal cancer (mCRC) that progressed following the application of bevacizumab-containing chemotherapy as a first-line treatment. Methods: This observational cohort study (OCS) analyzed the medical records of 73 patients with mCRC divided into a no-VEGFi group (n=48) and a VEGFi group (n=25). Progression-free survival (PFS) was the primary endpoint, and the overall survival (OS), objective response rate (ORR), disease control rate (DCR), and safety were secondary endpoints. Results: The results revealed that the PFS, ORR, and DCR of the VEGFi group were significantly superior to those of the no-VEGFi group, even in those with wild-type and mutant-type RAS or left-sided mCRC (all P0.05). Patients with primary left-sided lesions and continued use of VEGFi exhibited the most marked effect on PFS (P=0.001). No significant differences were observed in the incidence of grade 3 or 4 adverse events (AEs) between the two groups (P=0.133). Conclusions: These results support the use of VEGFi as a second-line treatment after bevacizumab beyond the initial progression in this OCS. Bevacizumab or aflibercept combined with second-line chemotherapy in mCRC has an acceptable safety profile and is relatively active. Regardless of the RAS gene type, VEGFi plus FOLOFX6 exhibited superior PFS to that of FLFOX6 as a second-line treatment, and a greater improvement in PFS was obtained for the left-sided lesions than for the right-sided lesions.